2007
DOI: 10.1111/j.1399-5448.2007.00230.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of type 1 diabetes mellitus in the 0- to 17-yr-old Israel population, 1997?2003

Abstract: The incidence of T1DM is increasing in the Israeli population, particularly in the Arab population. The culturally varied composition of the Israeli population provides important areas for future studies based on data collected in this national register.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 32 publications
3
14
1
2
Order By: Relevance
“…It is also consistent with that reported for WA [3.1% (95% CI 1.9, 4.2) for 1985–2002] and NSW [2.8% (95% CI 1.9, 3.8) for 1990–2002], but lower than that reported for Vic [9.3% (95% CI 2.5, 16.7) for 1999–2002] [9–11]. Furthermore, our study covers a later time period and the results indicate that the rising incidence has continued into this decade, in keeping with the few reports from other countries that extend beyond 2000 [2,3]. Although not all recent studies have shown an increase in incidence rates into this century [6,7], it is of concern that the increase in Finland has been exponential [5].…”
Section: Discussionsupporting
confidence: 92%
“…It is also consistent with that reported for WA [3.1% (95% CI 1.9, 4.2) for 1985–2002] and NSW [2.8% (95% CI 1.9, 3.8) for 1990–2002], but lower than that reported for Vic [9.3% (95% CI 2.5, 16.7) for 1999–2002] [9–11]. Furthermore, our study covers a later time period and the results indicate that the rising incidence has continued into this decade, in keeping with the few reports from other countries that extend beyond 2000 [2,3]. Although not all recent studies have shown an increase in incidence rates into this century [6,7], it is of concern that the increase in Finland has been exponential [5].…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, we did not identify a significant difference in the increase of diabetes incidence in the Jewish population compared with the non‐Jewish population, in spite of a genetically based difference in diabetes incidence between these ethnic groups . The incidence rate of type 1 diabetes is reportedly lower in non‐Jews than in Jews , which may account for lower rate of type 1 diabetes before war in the northern regions, where the non‐Jewish population is more abundant than in other regions of the country .…”
Section: Discussioncontrasting
confidence: 66%
“…Data on type 1 diabetes in children and adolescents were obtained from the Israel Juvenile Diabetes Register . This population‐based anonymous database that was founded in 1997 and conducted by The Israel IDDM Registry Study Group (IIRSG) is a joint project of the Israel Society of Pediatric Endocrinology and the Israel Center for Disease Control (ICDC).…”
Section: Methodsmentioning
confidence: 99%
“…In a reciprocally opposite pattern, the proportion of the sporadic cases was slightly decreased over the study period. It is conceivable that the familial cases share genetic susceptibility to T1D, considering the rarity of the disease in the general Israeli population . We can also assume that both familial and sporadic cases were exposed to similar environmental effects, considering the sizes of the geographical area (20 770 km 2 ) and the population in Israel (8.5 million people).…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings have also been reported in Israel. In a study based on the Israel Diabetes Registry, the annual rise was 3.6% between the years 1997 and 2003 . An even higher annual rise of 5.8% between the years 2000 and 2008 was reported in a study conducted in a large health organization in Israel …”
Section: Introductionmentioning
confidence: 88%